STATE-PRIVATE PARTNERSHIP IN THE FIELD OF MEDICAL SERVICES: PRINCIPLES, FORMS AND SIGNS - Shevchuk, Oleksandr; Shevchuk , Viktor; Matyukhina, Nataliya; Leiba, Olena; Harashchuk, Volodymyr (Revista Inclusiones, 2020)
The article explores the features of legal regulation of public-private partnerships in medical services provision. The regulatory legal acts on public-private partnership in provision of medical services should be divided into groups: general and special. The concept of "public-private partnership in the provision of medical services" is proposed, its principles, classification, forms, signs and advantages of their implementation are clarified. The methodology of this study is based on the use of general scientific and special methods of cognition. Comparative legal and comparative methods were used in the study of legislation governing the development of legal relations in the medical services field. The formal logical method helped us to establish the legal structure of such partnerships. The results of this work allowed us to determine the legal problems of legislation that arise during the public-private partnership implementation in the medical services field and the prospects for their elimination. It analyzes the current stage of public-private partnership in the provision of the medical services in Ukraine and the positive experience of individual countries of the European Union and the world, which can bring the quality of their delivery to a higher European level.